Implementasi Kebijakan Program Kampus Mengajar di SD Negeri Billa an Kecamatan Proppo Kabupaten Pamekasan - Fawaid Fawaid; Kendry Widiyanto (Pusat Riset dan Inovasi Nasional, 2023)
This research is based on the Teaching Campus Program which is a form of teaching assistance to empower students to help with the learning process in elementary schools. This qualitative research aims to explain the process of implementing the Teaching Campus Program Policy at SD Negei Billa an Proppo Pamekasan Madura. The methods used in this research are interviews and documentation. The focus of this research is the management of the Teaching Campus program by the university's MBKM team, the role of the District/City Education Office in the Teaching Campus program, as well as the role of schools and students in implementing the program. Documentation studies were obtained through the Teaching Campus guidebook and program policy files. Based on the research results, it shows that program management is lacking at the evaluation stage by the MBKM team, the role of the Education Department and program implementation carried out by students is quite good. The school gave a positive response to the program implemented by students. As well as teaching campuses for education and non-education students who are considered to have differences in the realization of work programs.